2015
DOI: 10.1364/oe.23.002857
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of orbital angular momentum through sub-wavelength waveguides

Abstract: Data capacity of optical communication is achieving its limit owing to the non-linear effect of optical fiber. As an effective alternative, light carrying orbital angular momentum can greatly increase the capacity for its unprecedented degree of freedom. We demonstrate the propagation of orbital angular momentum with topological charge of 1 and 2 in plasmonic circular waveguide with sub-wavelength diameter with little propagation loss of 2.73 dB/μm, which has never been observed in optical fibers with sub-wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Owing to its complex conductivity, graphene supports surface plasmon modes, accompanied with extremely short effective wavelength. Based on the exotic electronic transfer properties, graphene-based plasmonic waveguide devices and even Luneburg lens were constructed (see Figures 51(a Very recently, we demonstrated that spiral surface plasmon could be utilized to transfer orbital angular momentum (OAM) [253]. Graphene-based microtube was demonstrated to be able to accomplish this goal perfectly.…”
Section: Active Absorption Modulationmentioning
confidence: 99%
“…Owing to its complex conductivity, graphene supports surface plasmon modes, accompanied with extremely short effective wavelength. Based on the exotic electronic transfer properties, graphene-based plasmonic waveguide devices and even Luneburg lens were constructed (see Figures 51(a Very recently, we demonstrated that spiral surface plasmon could be utilized to transfer orbital angular momentum (OAM) [253]. Graphene-based microtube was demonstrated to be able to accomplish this goal perfectly.…”
Section: Active Absorption Modulationmentioning
confidence: 99%
“…In the last several years, the interaction of light with structured material was extensively studied to generate the required OAM states. The diverse structures include liquid crystal spatial light modulator (SLM) 8 , space-variant antenna arrays 12 , ring resonators 13 , nano-wires 14 15 and nano-holes 16 17 18 19 . Among these devices, plasmonic structures are of particular importance because the development requirement of integrated opto-electro system is becoming more and more urgent 20 21 22 23 24 .…”
mentioning
confidence: 99%
“…However, the employed devices are bulky and do not lend themselves to nanophotonic system integration. Recent progress in nano-fabrication facilitates the replacement of cumbersome optical components by ultrathin, planar metasurfaces or subwavelength waveguides [14][15][16][17][18][19][20][21][22]. Although successful generation of OAM-carrying beams, there are also some challenges that need to be solved.…”
Section: Introductionmentioning
confidence: 99%